The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.5993/ajhb.27.5.2
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Social Norms: Do Both Contribute to Predicting Leisure-time Exercise?

Abstract: Social support and social norms contribute independently to our understanding of variation in the frequency of strenuous leisure-time exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 0 publications
8
68
2
6
Order By: Relevance
“…These were adapted from the perceived social support measured used in a study by Okun et al (2003) that included information and esteem support. The first score, was created by summing across 4 questions, and assessed the likelihood of seeking informational support when uncertainties with food safety behaviour arise, when developing intentions (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were adapted from the perceived social support measured used in a study by Okun et al (2003) that included information and esteem support. The first score, was created by summing across 4 questions, and assessed the likelihood of seeking informational support when uncertainties with food safety behaviour arise, when developing intentions (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that patients recovering from myocardial infarction were less likely to maintain regular activity, if they had low perceived social support (Luszczynska & Sutton, 2006). Higher social support has also been shown to significantly predict strenuous exercise (Okun, Ruehlman, Karoly, Lutz, Fairlholme, & Schaub, 2003). If support can reduce the effects of difficulties when maintaining health behaviours, then it may be an additional predictor of food safety intention and behaviour.…”
Section: Originality/valuementioning
confidence: 99%
“…Some studies have found that social support influences students' PBC, which in turn predicts the intent to partake in LTPA SOCIAL NETWORK SITES AND PHYSICAL ACTIVITY (Courneya & McAuley, 1995;Okun et al, 2003), whereas another study suggested social support should replace subjective norm in TPB to directly predict intention to participate in LTPA (Courneya, Plotnikoff, Hotz, & Birkett, 2000). Furthermore, even less knowledge exists about the effect of social support from contacts on SNSs on students' intention to participate in…”
Section: Tpb Constructsmentioning
confidence: 99%
“…Okun et al (2003) found that social norms were a significant predictor of physical activity in the general population, but that an even stronger predictor was social support. Social support for physical activity from friends and family has also been positively associated with physical activity levels in cancer survivors (Eyler et al, 1999;Rogers et al, 2008).…”
Section: Addressing Psychological Barriers To Physical Activitymentioning
confidence: 99%